Factors Influencing Health Care Workers' Willingness to Respond to Duty during Infectious Disease Outbreaks and Bioterrorist Events: An Integrative Review. Issue 3 (23rd June 2021) - Murray, Eleanor J.; Mason, Matt; Sparke, Vanessa; Zimmerman, Peta-Anne P.
Abstract: Background: Infectious disease emergencies are increasingly becoming part of the health care delivery landscape, having implications to not only individuals and the public, but also on those expected to respond to these emergencies. Health care workers (HCWs) are perhaps the most important asset in an infectious disease emergency, yet these individuals have their own barriers and facilitators to them being willing or able to respond. Aim: The purpose of this review was to identify factors affecting HCW willingness to respond (WTR) to duty during infectious disease outbreaks and/or bioterrorist events. Methods: An integrative literature review methodology was utilized to conduct a structured search of the literature including CINAHL, Medline, Embase, and PubMed databases using key terms and phrases. PRISMA guidelines were used to report the search outcomes and all eligible literature was screened with those included in the final review collated and appraised using a quality assessment tool. Results: A total of 149 papers were identified from the database search. Forty papers were relevant following screening, which highlighted facilitators of WTR to include: availability of personal protective equipment (PPE)/vaccine, level of training, professional ethics, family and personal safety, and worker support systems. A number of barriers were reported to prevent WTR for HCWs, such as: concern and perceived risk, interpersonal factors, job-level factors, and outbreak characteristics. Conclusions: By comprehensively identifying the facilitators and barriers to HCWs' WTR during infectious disease outbreaks and/or bioterrorist events, strategies can be identified and implemented to improve WTR and thus improve HCW and public safety.